Impact of weather on lowland rice cultivation and planning decisions over humid tropical India - DAS, H. P.; GAONKAR, S. B. (MAUSAM, 2000)
The present study investigates the effect of the climatic environment on three different varieties of paddy. Crop coefficient in different stages of growth, the consumptive uses and radiation use efficiency has been determined and discussed in each case. Ideal date which could give optimum yield, has been determined in two varieties. The yield was correlated with weather parameters for each of the phases of the crop growth by forward ranking method and a statistical prediction model developed. Path analysis was applied to the predictors thus selected and direct and indirect contribution of the predictors to yield determined and discussed.